Emplacement of a felsic dyke swarm during progressive heterogeneous deformation, Eastern Elba Dyke Complex (Island of Elba, Italy). (June 2022) - Papeschi, S.; Mazzarini, F.; Musumeci, G.; Cruden, A.R.
Abstract: Magmatic and sub-solidus fabrics in intrusive rocks are frequently used to infer the relative timing of deformation with respect to magma emplacement and cooling. Here, we describe the relationships between strain and fabric development in leucogranite sheets (pegmatite, aplite) emplaced into shear zones that localized post-thermal peak deformation in the contact aureole of an upper crustal pluton (<0.2 GPa) on the Island of Elba, Italy. The leucogranite sheets present igneous, mylonitic, and cataclastic fabrics. Detailed meso- and microscopic structural analysis suggests that the dykes emplaced in the shear zones behaved as competent, rigid bodies during mylonitic deformation of the host rocks. Thermal modelling indicates that emplacement and cooling of the sheets occurred very rapidly (a few days to years) compared to typical tectonic strain rates and strain accumulation timescales in the host rocks. Such a fast cooling does not allow melt or magma-induced thermal softening in the host rocks during deformation. The development of mylonitic and cataclastic fabrics in the dykes was controlled by the localized activation of fluid-controlled reaction softening mechanisms (mylonitic fabric) and embrittlement during cooling in sites of high-strain (cataclastic fabric). We show that a broad spectrum of fabrics can form in igneous sheet intrusions emplaced at the same time and crustal level. The coexistence of isotropic (non-foliated igneous) versus anisotropic (mylonitic and cataclastic) fabrics in igneous sheet intrusions should therefore be evaluated in terms of tectonic strain rates, cooling rates, thermal state of the host, distribution of heterogeneous strain, and activation of strain softening mechanisms. Our observations highlight that the concepts of pre-, syn-, late- and post-tectonic fabrics in intrusive igneous rocks should be used with caution when interpreting relative timing relationships between deformation and magmatism. Highlights: Coeval igneous sheets emplaced in shear zones record different deformation fabrics. Cooling rates of igneous sheets are faster than tectonic strain rates. Rapidly crystallizing dykes produce rheological heterogeneities within shear zones. The development of mylonites in 'strong' igneous sheets requires strain softening. Localized embrittlement during cooling produces cataclastic igneous sheets.